Pain and Personality: Do Individuals with Different Forms of Chronic Pain Exhibit a Mutual Personality?. Issue 4 (10th April 2015) - Gustin, Sylvia M.; Burke, Lucinda A.; Peck, Chris C.; Murray, Greg M.; Henderson, Luke A.
Abstract: The role of personality in the experience of chronic pain is a growing field, with endless debate regarding the existence of a "pain personality". This study aims to compare different chronic pain types and consolidate the existence of a common personality. Thirty‐two females with chronic orofacial pain and 37 age‐matched healthy females were assessed with the Temperament and Character Inventory‐Revised. Chronic pain subjects had either trigeminal neuropathy (neuropathic pain) or temporomandibular disorders (nociceptive pain). This study revealed that individuals with different chronic pain types exhibit a mutual personality profile encompassing significantly higher scores in Harm Avoidance and significantly lower scores in Self‐Directedness when compared to healthy subjects. In fact, this combination is associated with Cluster C personality disorders. In conclusion, our study reveals that irrespective of type, chronic pain may be associated with Cluster C personality disorders. Indeed, there has never been empirical evidence in the past to suggest that chronic pain as an overall concept is associated with any particular personality disorders. Therefore, a potential future avenue of chronic pain treatment may lie in targeting particular personality aspects and shift the target of pain‐relieving treatments from sensory and psychologically state focused to psychologically trait focused.